2021
DOI: 10.3390/ijerph182312653
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Esports Participation Intention: The Development and Psychometric Properties of the Theory of Planned Behavior-Based Esports Intention Questionnaire (TPB-Esport-Q)

Abstract: Background: Esports is seen as an emerging industry that has enjoyed a surge in popularity worldwide. As a result, researchers have undertaken studies to try to understand the motivations and factors that impact Esports gameplay. Given the extensive utilization of TPB in many research projects to conceptualize and predict various behaviors, the current study aimed to further extend this theory to the Esports context by developing and validating an instrument that can illustrate the factors that impact the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 24 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…The Esports Participation Questionnaire [62] uses standardized questions, tapping into TPB constructs to measure participants' attitudes, subjective norms, and perceived behavioral control (direct measures), and indirect measures as suggested by Ajzen [16]. The questionnaire was on a 5point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Esports Participation Questionnaire [62] uses standardized questions, tapping into TPB constructs to measure participants' attitudes, subjective norms, and perceived behavioral control (direct measures), and indirect measures as suggested by Ajzen [16]. The questionnaire was on a 5point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Among the secondary school students, fortyeight of them had participated in Esports in the last six months. Because according to the psychometric properties measurement of TPB mode [62], good fit when separated secondary school and university samples. Therefore, in this study, the two samples of secondary schools and universities were analyzed separately.…”
Section: Demographicsmentioning
confidence: 99%
“…In this study, a questionnaire developed by the researcher was used for data collection before and after the educational intervention [ 27 , 28 ]. This questionnaire comprised 42 items in 3 parts.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have identified various gaps in research on eSports [10][11][12][13] including the lack of studies examining (a) factors related to participation in eSports, such as the determinants or motivation of participation, among players of various ages (e.g., older adults) and (b) identifying factors, psychological or physiological, that facilitate or impede healthy behaviors in amateur participants (e.g., amateur older players). In HK, Leung et al [14] were the first to examine the public's (1556 adults aged ≥ 18 years) understanding of and perceptions regarding eSports. The authors reported that 60% of the 292 randomly interviewed older adults aged ≥ 65 years (out of 1556 participants) supported government funding for eSports development in HK.…”
Section: Introductionmentioning
confidence: 99%
“…Various models or theories have been adopted to explain behavioral intention and technology use, including the Technology Acceptance Model (TAM) [15], Unified Theory of Acceptance and Use of Technology (UTAUT) [16], Self-Determination Theory (SDT) [17], and Theory of Planned Behavior (TPB) [18]. Some of them have been applied to investigate gaming in older adults, including the TAM [15], UTAUT [16], SDT [17], and TPB [14,19,20]. The TPB explains how individuals' attitudes and beliefs regarding behavior, subjective norm, and perceived control affect their participation in health-relevant behaviors [21].…”
Section: Introductionmentioning
confidence: 99%